Dawr al-Sulṭān Zayn al-‘Ābidīn fī Nashr al-Islām fī Sulṭānah al-Tarnātī fī al-Qarn al-Rābī’ ‘Ashr al-Mīlādīyah - Marasabessy, Bunyamin (Studia Islamika, 2006)
This article looks closely at the process of the growth and development of Islam in Malaku, focusing on the role of one of the rulers of Tarnate, Sultan Zainal Abidin, in this process. As the oldest son of the previous ruler, Kolano Marhum, Zainal Abidin was the logical choice to become the 19th Sultan of the Ternate Kingdom; this was bolstered by the fact that he inherited all of his father's good character traits. Zainal Abidin ruled the Kingdom of Ternate from 1468 until1500. The northern area of Maluku (Ternate-Halamahera) is a region which is rich in spices. It was this that brought merchants on masse from the Middle East to Maluku. Further to their business activities, the Arab merchants also carried out dakwah activities.DOI: 10.15408/sdi.v13i3.562